2014
DOI: 10.1007/s12262-014-1112-8
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Strip Test as an Independent Predictor in Acute Pancreatitis

Abstract: Plasma procalcitonin (PCT) is a highly specific marker for the diagnosis of bacterial infection and sepsis. Studies have demonstrated its role in the setting of sepsis and acute pancreatitis. This study aims to analyze and compare the prognostic efficacy of plasma procalcitonin strip test in acute pancreatitis. A prospective study was conducted in the department of general surgery from June 2012 to June 2013. Plasma procalcitonin was estimated by the semiquantitative strip test. The study included a total of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
0
13
0
1
Order By: Relevance
“…Severe AP is known to be associated with sepsis, infected pancreatic necrosis, and multiorgan failure, and PCT can be used as an early tool in the prognosis of AP [130,131]. For a faster result, PCT levels can be measured by a semiquantitative strip test with a cut-off level of 0.5 ng/mL [132] while other studies report a better cut-off of 2 ng/mL [133]. An increased PCT level in patients with AP was found to be indicative of severity, pancreatic necrosis, and organ failure.…”
Section: Procalcitoninmentioning
confidence: 99%
“…Severe AP is known to be associated with sepsis, infected pancreatic necrosis, and multiorgan failure, and PCT can be used as an early tool in the prognosis of AP [130,131]. For a faster result, PCT levels can be measured by a semiquantitative strip test with a cut-off level of 0.5 ng/mL [132] while other studies report a better cut-off of 2 ng/mL [133]. An increased PCT level in patients with AP was found to be indicative of severity, pancreatic necrosis, and organ failure.…”
Section: Procalcitoninmentioning
confidence: 99%
“…In a study of 75 patients -of which 12 had severe acute pancreatitis-while investigating the predictive power of procalcitonin levels on severe acute pancreatitis, it was found that procalcitonin levels on admission and at 48 th hour had limited predictive power on biliary pancreatitis and severe pancreatitis (26). However, in another study on 50 patients, the predictive power of procalcitonin levels determined by strip test for duration of hospitalization, the need for intensive care, the necessity of antibiotic therapy, and the development of severe acute pancreatitis was examined, and it was found that procalcitonin levels showed higher correlation than CRP and leukocyte levels (15). In the present study, cut-off value of NLR at 48 th hour for predicting the severity of pancreatitis was 7.48, and its predictive power was shown to be at a level consistent with other studies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of prognostic scores according to the revised Atlanta classification is presented in Table 5. The values of 15 mg/dL and 0.5 ng/mL for CRP and procalcitonin were used in reference to previous publications in the literature (10,15). There are different cut-off values in the literature for NLR (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations